Band spectrum transformation and temperature dependences of thermoelectric power of Hg₁-xRxBa₂Ca₂Cu₃ O₈+δ system - Babych, O.; Gabriel, I.; Lutsiv, R.; Matviyiv, M.; Vasyuk, M. (Condensed Matter Physics, 2011)
Temperature dependences of thermoelectric power S(T) at T>Tc of the Hg-based high temperature superconductors Hg₁-xRxBa₂Ca₂Cu₃O₈+δ (R=Re, Pb) have been analyzed with accounting for strong scattering of charge carriers. Transformation of parameters of a narrow conducting band in the region of the Fermi level was studied. The existence of correlation between the effective bandwidth and the temperature of a superconductive transition Tc is shown.